Implications of the Presidential Threshold Implementation on the Formation of Cartel Coalitions - Rahmat Muhajir Nugroho (Kosmik Hukum, 2024)
The threshold for presidential candidacy as a condition for nominating candidates for President and Vice President in the General Election in Indonesia creates constitutional problems. Political parties that have been designated as election participants cannot immediately nominate pairs of candidates for President and Vice President because there are additional requirements outside of the constitutional provisions, namely that political parties must have 20% of the DPR RI seats or 25% of the valid national votes resulting from the Legislative Election in the previous five years. This research aims to analyze the implications of implementing the Presidential Threshold on the formation of cartel coalitions. The research method is normative legal research using primary, secondary, and tertiary legal materials. Apart from limiting the rights of political parties, these threshold provisions also have implications for the formation of cartel coalitions, so they are very dominant in Parliament. This research concludes that setting the threshold for nominations for President and Vice President has implications for the formation of large coalitions (oversized coalitions) in government, even political cartels, thus opening opportunities for oligarchs to intervene in government.Keywords: Election, Presidential Threshold, Cartel